ANALYSIS OF COHESION ERRORS IN ALEXANDER HERY'S SHARIA ACCOUNTING BOOKS WITH A FOCUS ON STUDYING THE USE OF INTERSENTENCE CONJUNCTIONS - N Tatat Hernawati; Ika Mustika (IKIP Siliwangi, 2022)
The number of errors in the use of conjunctions in writing academic books makes the authors interested in carrying out research related to the cohesion of a paragraph in academic books. The purpose of this research is to describe the cohesion errors that exist in Alexander Hery's Islamic Accounting book. The method used is a qualitative method with a descriptive approach. The data source of this research is Alexander Hery's Islamic Accounting book. The data of this research are sentences in paragraphs that contain cohesion errors. Data analysis was carried out using descriptive qualitative analysis techniques. The results of this study indicate that there is cohesion in the use of conjunctions between sentences twelve times in the Islamic Accounting book. Researchers found an error in the use of the word